Pendidikan Multikultural menurut Sayyid Quṭb dalam Tafsīr fī Ẓilāl Al-Qur’ān - Hanan Putri Nasution (Studi Multidisipliner: Jurnal Kajian Keislaman, 2020)
The concept of multicultural education’s Sayyid Quṭb starts from the verses of the Qur'an which explain diversity, as well as several traditions that narrate the patterns and interactions of the Prophet who live in diversity. This article examines a topic of multicultural education through the perspective of Sayyid Quṭb in his interpretation book Fī Ẓilāl Al-Qur’ān, focusing on several verses in Surah Al-Baqarah (2) verse 62, Surah Hūd (11) verse 118 , Surah Al-Rūm (30) verse 22, Surah Al-Fatḥ (48) verse 29, Surah Al-Ḥujurāt (49) verses 9, 10, 11, and 13. Multicultural education according to Quṭb in Tafsīr Fī Ẓilāl Al-Qur’ān is a doctrine in which one recognizes diversity and difference as sunnatullāh, and is also a sign of God's power. God's determination for this diversity has a goal so that people can get to know each other, brothers, work together, improve each other, give each other benefits and also be compassionate so as to create a harmonious, safe and peaceful life. Sayyid Quṭb hisself views multicultural education as a character of Islamic religion, in his interpretation Sayyid Quṭb even condemns people who are fanatical about certain tribes or groups by calling them as a jahiliyyah.